Evaluasi Workshop Stimulasi Deteksi Intervensi Dini Tumbuh Kembang Guru PAUD di Wilayah Kecamatan Barat Kabupaten Magetan - N. Surtinah; Tutiek Herlina (FORIKES, 2020)
Background: The Ministry of Health of the Republic of Indonesia in collaboration with the Indonesian Pediatrician Association has developed stimulation, detection and early intervention instruments for growth and development for children aged 0 years to 6 years, which are described in the Guidelines for the Early Stimulation, Detection and Intervention for Growth and Development of Children (SDIDTK) at the basic health service level. The results of a preliminary study in Barat Subdistrict obtained SDIDTK coverage in May 2018, complete babies were 86% below the target of 97%. The coverage of plenary children under five is 97% of the 100% target, and the coverage of plenary preschool children is 82% of the 100% target. As an effort to increase SDIDTK coverage, SDIDTK workshops were held for PAUD teachers who manage toddlers. Objective: To evaluate the SDIDTK Workshop on PAUD teachers in the Barat District, Magetan Regency. Methods: This type of pre-experimental research with a one group pretest posttest design. The research sample was all 60 Barat Subdistrict PAUD teachers. Sampling technique using total sampling technique, research variable knowledge about SDIDTK. Data collection by questionnaire. Data analysis with paired statistical test T test α 0.05. presentation of data in the form of a frequency distribution table. Results: most (73.33%) of the PAUD teachers' education level was high, S1 degree. The average pretest result was 38.42 and the average post-test result was 75.17. The results of the statistical test showed that the value of p = 0.000 (p≤0.05), it can be concluded that there is a difference between before and after receiving the SDIDTK workshop material. Conclusion: SDIDTK workshops are effective in increasing the knowledge of PAUD teachers in Barat District, Magetan Regency. Advice for. PAUD teachers in Barat sub-district, Magetan Regency can apply SDIDTK to students. The Puskesmas Barats expected to monitor the achievement of SDIDTK implementation targets in the West District area. Keywords: SDIDTK; PAUD teacher ABSTRAK Latar belakang: Kementerian Kesehatan Republik Indonesia bekerja sama dengan Ikatan Dokter Anak Indonesia telah menyusun instrumen stimulasi, deteksi dan intervensi dini tumbuh kembang untuk anak umur 0 tahun sampai dengan 6 tahun, yang diuraikan dalam Pedoman Pelaksanaan Stimulasi, Deteksi dan Intervensi Dini Tumbuh Kembang (SDIDTK) Anak di tingkat pelayanan kesehatan dasar. Hasil studi pendahuluan di Kecamatan Barat diperoleh cakupan SDIDTK Bulan Mei 2018 bayi paripurna 86% di bawah target 97%. Cakupan anak balita paripurna 97% dari target 100%, dan cakupan anak prasekolah paripurna 82% dari target 100%. Sebagai upaya peningkatan cakupan SDIDTK maka dilaksanakan workshop SDIDTK pada guru PAUD yang mengelola anak balita. Tujuan: mengevaluasi Workshop SDIDTK bagi guru PAUD di wilayah Kecamatan Barat Kabupaten Magetan. Metode: jenis penelitian pra eksperimen dengan rancangan one group pretes postes. Sampel penelitian adalah seluruh guru PAUD Kecamatan Barat sebanyak 60 orang. Tehnik sampling menggunakan tehnik total sampling, variabel penelitian pengetahuan tentang SDIDTK. Pengumpulan data dengan kuesioner. Analisa data dengan uji statistic paired T tes α 0.05. penyajian data dalam bentuk tabel distribusi frekuensi. Hasil: sebagian besar (73,33%) tingkat pendidikan guru PAUD termasuk tinggi yaitu S1. Rata-rata hasil pretes 38,42 dan rata-rata hasil postes 75.17. Hasil uji statistik diperoleh nilai p=0.000 (p≤0.05) maka dapat disimpulkan ada perbedaan antara sebelum dan setelah mendapatkan materi workshop SDIDTK. Kesimpulan: workshop SDIDTK efektif meningkatkan pengetahuan Guru PAUD di Kecamatan Barat Kabupaten Magetan. Saran bagi. Guru PAUD di kecamatan Barat Kabupaten Magetan dapat menerapkan SDIDTK pada murid. Puskesmas Barat diharapkan memantau pencapaian target pelaksanaan SDIDTK di wilayah Kecamatan Barat. Kata kunci: SDIDTK; guru PAUD